Perceived Training Needs of Teachers in Early Childhood Assessment: - Olowe, Peter Kayode; Rasheed, Simideleola T (Indonesian Journal of Early Childhood Education Studies, 2019)
The issue of access to quality early childhood development, care and pre-primary education was captured in Target 2 of Sustainable Development Goal 4 (SDG 4) because the early childhood period is critical to childrenâ€™s learning and development. One of the ways by which teachers can provide children with the quality early childhood development and pre-primary education is through effective early childhood assessment. Assessment is extremely important for determining childrenâ€™s learning and developmental progress. In spite of this, teachers do not carry out effective assessment in many pre-primary schools in Nigeria. While previous studies have recommended that the teachers should be trained, research efforts have not been targeted at finding out if the teachers themselves perceive that they need training in early childhood assessment practices. Consequently, this study examined if teachers in Ondo West Local Government Area perceive that they need training in early childhood assessment. The survey research design was adopted. Sample comprised two hundred and eighty eight pre-primary schools teachers from both public and private schools. An instrument titled â€œEarly Childhood Assessment Training Needs Questionnaire (ECATNQ)â€ was used. Data was analysed using percentage, mean and standard deviation. Pre-primary school teachers perceived that they need training in early childhood assessment. The implications of this finding for the achievement of Target 2 of SDG 4 were discussed. It was recommended among others that Ondo State Universal Basic Board and private school administrators should organise workshop and seminars for pre-primary school teachers on early childhood assessment.